Co-Creative Action Research Experiments—A Careful Method for Causal Inference and Societal Impact - Arjen van Witteloostuijn; Nele Cannaerts; Wim Coreynen; Zainab Noor el Hejazi; Joeri van Hugten; Ellen Loots; Hendrik Slabbinck; Johanna Vanderstraeten (Social Sciences, 2020)
The rigor-versus-relevance debate in the world of academia is, by now, an old-time classic that does not seem to go away so easily. The grassroots movement Responsible Research in Business and Management, for instance, is a very active and prominent advocate of the need to change current research practices in the management domain, broadly defined. One of its main critiques is that current research practices are not apt to address day-to-day management challenges, nor do they allow such management challenges to feed into academic research. In this paper, we address this issue, and present a research design, referred to as CARE, that is aimed at building a bridge from rigor to relevance, and vice versa. In so doing, we offer a template for conducting rigorous research with immediate impact, contributing to solving issues that businesses are struggling with through a design that facilitates causal inference.